SEMIQUANTITATIVE EVALUATION OF 99MTCTRODAT1 BINDING POTENTIAL BY TWO METHODS OF SPECT IMAGE RECONSTRUCTION. (Brazilian Journal of Radiation Sciences (BJRS), 2019)
TRODAT-1 is a radiopharmaceutical derived from tropane and linked to tecnecium-99m ([99mTc] TRODAT-1) has been used in studies of dopamine transporter (DAT) in central nervous system. Associated with the SPECT technique of acquisition, is able to detect changes in neurological disorders like Parkinson´s disease, evaluating the binding potential (BP) of DAT. The aim of this study was to evaluate the influence of the image reconstruction methods, Filtered Back Projection (FBP) and iterative reconstruction (OSEM), in BP values at the striatal region in 30 healthy volunteers. Images were analyzed by visual inspection and semi-quantitative analysis. Regions of interest (ROI) were made over striatal areas on both sides. Nonparametric Wilcoxon statistical analysis was performed between the BP values from the FBP and OSEM methods. Our results showed that the reconstruction methods have a statistical significant BP values difference in the total striatum (Z = -2,2787 p = 0.005), right striatum (Z = -2,602 p = 0.009) and left striatum (Z= 2,746 p = 0.006). The effect size was calculated to see if there influence in this test: the "large effect size" for all measurements was observed (total striatum r= -0.51; right striatum r= -0.48; left striatum r= -0.50). FBP is the usual method of reconstruction for brain SPECT images, and our results showed influence of the OSEM method in BP. It is concluded that the method of image reconstruction adopted should be standardized to avoid incorrect evaluations of BP values using [99mTc]TRODAT-1.